The Role of Human Resources in Improving Employee Welfare and Job Satisfaction - Sofiatur Rizkianti; Muhammad, Muhammad (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
In a dynamic and competitive work environment, HR plays a crucial role in creating policies and programs that support employee well-being. Some strategies implemented include training and development, work-life balance programs, and rewards and recognition. Training and development help employees enhance their skills and competencies, positively impacting job satisfaction. Work-life balance programs, such as flexible working hours and mental health support, contribute to employees' emotional and physical well-being. Fair rewards and recognition increase employee motivation and engagement. The results of these roles indicate that high well-being and job satisfaction can boost productivity, reduce turnover rates, and create a positive work culture. This article asserts that a proactive and strategic HR role is essential in creating a work environment that supports employee well-being and job satisfaction, which continues to grow. Success in creating a conducive work environment will result in higher loyalty, improve team performance, and strengthen the company's competitiveness in an increasingly competitive market. In this context, the HR management function does not only focus on administrative aspects, but must also be able to act as a strategic partner in organizational decision-making. This includes the role of designing organizational strategy, managing change, and building an adaptive and collaborative work culture. With a people-oriented approach, HR can be the main driver in organizational transformation towards sustainable excellence. Furthermore, the importance of data and analytics in HR decision-making cannot be ignored. Through proper data analysis, organizations can identify trends, evaluate program effectiveness, and design more targeted interventions to improve employee well-being. This evidence-based approach strengthens the role of HR as a strategic and results-based function. Thus, it can be concluded that the success of an organization is highly dependent on the extent to which the role of HR is carried out strategically and oriented towards employee well-being. Investment in human resources is not only a form of corporate social responsibility, but also a smart and competitive business strategy.